2013
DOI: 10.1177/1469605312455768
|View full text |Cite
|
Sign up to set email alerts
|

Social memory and ritual performance

Abstract: This article is concerned with archaeological evidence for the mechanisms by which group memory is transmitted. Specifically, how do natural places such as caves and rock shelters retain their status as foci for ritual activity? It draws upon recent social and archaeological theory around embodied memory; in particular, Connerton's (1989) division of memory claims into three kinds. These are: personal memory claims, cognitive memory claims and habit-memory. It is argued that cognitive memory claims and habit-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…As noted also by Connerton (1989) and Peterson (2013), for Mapoon, I found that Elders and missionary families transmit memory of trauma to others through these events and interpretation of these monuments. The acts of interpretation of monuments and commemoration of these dark heritage places are acts of power by Elders to also control how these places are remembered and reified in future and interpreted by outsiders.…”
Section: Cultural Heritage Memory and Traumasupporting
confidence: 65%
See 1 more Smart Citation
“…As noted also by Connerton (1989) and Peterson (2013), for Mapoon, I found that Elders and missionary families transmit memory of trauma to others through these events and interpretation of these monuments. The acts of interpretation of monuments and commemoration of these dark heritage places are acts of power by Elders to also control how these places are remembered and reified in future and interpreted by outsiders.…”
Section: Cultural Heritage Memory and Traumasupporting
confidence: 65%
“…Memory studies is a well-established field in social sciences and sciences, with research examining the cognitive abilities and physiological functions of the brain and memory ranging to cultural studies of memory, including social memory, historical memory and collective memory (Bell 2006;Blatz and Ross 2009;Boyer and Wertsch 2009;Edkins 2003;Jones 2007;Jones and Russell 2012;Kidron 2013;Maček and Ebooks 2014;Nünning and Erll 2008;Peterson 2013;Whitehead 2009). This study explores the transmission of memory (including recollections of traumatic history) through ritual and social practices in cultural heritage places as related in Connerton (1989) and Peterson (2013). This study delves into social and collective memory, where memories "sustain a distinctive identity, which is what social groups need, maintain and transmit to further generations" and works with memory as a cultural process (Boyer 2009:9).…”
Section: Memorymentioning
confidence: 99%
“…De este modo, en su articulación con los sepulcros u obras de arte rupestre, las prácticas comensales sumaron un sentido específicamente conmemorativo. La repetición pautada del ritual habría contribuido activamente a la construcción de la memoria social, incluyendo su eventual transmisión, invención o transformación, así como su eliminación u olvido (Jones, 2007;Mills y Walker, 2008;Moore, 2010;Peterson, 2013).…”
Section: Integración De Datos Y Conclusionesunclassified
“…[7]. The connection between social memory and ritual performance was studied by contemporary British archaeologist R. Peterson, who writes about archaeological evidence for the mechanisms by which group memory is transferred [8].…”
Section: Theoretical Frameworkmentioning
confidence: 99%